Stated motivation for share buybacks in Malaysia - Zainudin, Nasruddin; Regupathi, Angappan (Institut Bank-Bank Malaysia, 2003)
Share buyback is a recent phenomenon in the Malaysia capital market.It has only been allowed since 1997 as a response to the currency crisis to shore up market share prices.This study explores companies states motivations for undertaking share buyback.It examines' 40 companies' circulars to shareholders between October 1999 and May 2002, to identify the companies' stated motivations for undertaking share buybacks.Apart from identifying the stated motivations, the study also detects motivations that are the most stated, and those that appear to be accorded greater emphasis.The findings, with the use of non-parametric statistics, indicate that out of the nine motivations for share buybacks, four motivations are hardly stated by the companies.These include (1)distribute cash, (2) issue stocks under the Employee Stock Option Schemes, (3) change capital structure, and (4)anti-takeover measure.The other five motivations are widely stated, and these are (1) pay stock dividend, (2)investment opportunity, (3) stabilise share price, (4)use surplus cash, and (5) increase shareholder return/EPS.The first of these widely stated motivations appears to be given less relative emphasis because it is stated consistently later in the circulars to shareholders, compared to the other widely stated motivations.